2019
DOI: 10.29228/turkishstudies.39294
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenleri̇n Eği̇ti̇m Bi̇li̇şi̇m Aği (Eba) Tutumlarinin İncelenmesi̇

Abstract: ÖZEğitim Bilişim Ağı (EBA), Millî Eğitim Bakanlığının Yenilik ve Eğitim Teknolojileri Genel Müdürlüğü tarafından geliştirilen, öğrenciler ve öğretmenlerin ücretsiz olarak yararlanabildikleri çevrimiçi bir sosyal eğitim platformudur. Bu platform dersler, içerikler, yarışmalar, uygulamalar, çeşitli eğitsel dosyalar, e-kurs imkânları gibi çeşitli eğitsel içeriklerle yazı, resim, ses ve video gibi farklı türdeki bilgi kaynaklarını barındırmaktadır. Temel işlevi öğretmen ve öğrencilerin teknolojiden yararlanarak et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
1
Order By: Relevance
“…When the sub-dimensions are analyzed specifically, it is seen that the necessity of EBA has higher ratios than the applicability dimension of EBA. When the studies carried out before and during the pandemic are examined, it is seen that results parallel to this study were obtained (Varışoğlu, 2019;Aztekin, 2020;Şireci, 2021;Tutar, 2015;Yılmaz, 2019;Kuloğlu, 2018;Karbeyaz & Kurt, 2020). However, considering the studies conducted until 2021 examining the attitudes of teachers towards the Education Information Network, this study is the study in which the lowest EBA attitude scores of teachers were obtained.…”
Section: Conclusion and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…When the sub-dimensions are analyzed specifically, it is seen that the necessity of EBA has higher ratios than the applicability dimension of EBA. When the studies carried out before and during the pandemic are examined, it is seen that results parallel to this study were obtained (Varışoğlu, 2019;Aztekin, 2020;Şireci, 2021;Tutar, 2015;Yılmaz, 2019;Kuloğlu, 2018;Karbeyaz & Kurt, 2020). However, considering the studies conducted until 2021 examining the attitudes of teachers towards the Education Information Network, this study is the study in which the lowest EBA attitude scores of teachers were obtained.…”
Section: Conclusion and Discussionsupporting
confidence: 72%
“…The Cronbach Alpha, internal consistency test, was used to measure the scale's reliability. The reliability coefficient of the EBA Attitude scale was calculated as 0.950 in the study of Uğurlu and Gürsoy (2018), 0.894 in the study of Varışoğlu (2019), 0.950 in the study of Akça (2021), and as 0.957 in this study. The EBA Attitude scale, for which validity and reliability analyzes were made, consists of 2 sub-dimensions: "Necessity of EBA (24 items)" and "Applicability of EBA (6 items)".…”
Section: Eba Attitude Scalementioning
confidence: 52%
“…Considering the results obtained in this study, in the obligation category, the lack of negative perception of teachers towards distance education may be due to the higher level of readiness than students and parents. In a study that examines teachers' perceptions of the Education Information Network they have used since 2012, it was concluded that teachers have a positive perception (Varışoğlu, 2019). The Education Information Network, designed by the Ministry of National Education, is an online social education platform.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Öğretmenler ayrıca sistemdeki özelliklerin dersleri için kullanışlı ve işlevsel olarak çalıştığını belirtmektedirler. Varışoğlu(2019) öğretmenlerin EBA'ya karşı tutumlarını incelediği çalışmasında, senkron olarak oluşturulmuş sanal sınıf etkinliklerinde kullanım kolaylığı ve yarar algısının, öğretmenleri bu sistemi daha çok kullanmaya teşvik edeceği sonucuna ulaşmıştır. EBA Canlı Ders sisteminde bir ders için 30 dakika süre verilmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified